A new reactive absorption model using extents of reaction and activities. I. Application to Alkaline-salts-CO2 systems. (15th April 2023) - Delgado, Serena; Gaunand, Alain; Coquelet, Christophe; Cadours, Renaud; Volpi, Céline
Highlights: A new general steady-state absorption model is proposed. Diffusion flux, reaction rates and physical and chemical equilibria representation considers solution non ideality. The number of differential equations in the reactive absorption problem is reduced by using extents of reactions. A unique activity-based rate constant for CO2 reaction with HO – in all alkaline (Li +, Na + and K + ) solutions is derived. The method predicts available CO2 absorption flux data with a 12% AAD. Abstract: CO2 absorption into basic aqueous solutions is widely used for CO2 separation from gas streams (e.g., for natural gas purification). CO2 loading and ionic strength increase significantly along industrial columns. In absorption modelling, deviation from ideality should then be considered. This study implements a general steady-state model for reactive gas–liquid absorption. Firstly, equilibrium relations, Nernst-Planck diffusion fluxes and reaction rates are written based on activities. Secondly, local fluxes are related by stochiometric constraints through extents of reaction. In a first case study, the model, together with an appropriate thermodynamic representation, was applied with the stagnant film theory (Whitman, 1923 ) to alkaline salts-water-CO2 systems. The following Arrhenius expression was found for the direct kinetic constant of reaction CO2  + HO – ↔ HCO3 – : ln k (m 3 mol −1 s −1 ) = 19.84–5248.8/T (K) – 12% overall AAD. This kinetic law can be used in any system involving this reaction (e.g., aqueous amine solutions). This part I paves the way to the further study of CO2 absorption into aqueous amine solutions.